Predictable April 2025 extreme dust storm in Southern China - Wenqi Zhang; Mei Chong; Huiwen Xiao; Shengkai Wang; Qiang Zhang; Xi Chen; Lin Wang (Science Bulletin, 2026)

Preliminary Study on the Structure of Fungal Communities in Artificial Reef Areas in the Northern Yellow Sea - Jiamin Yan; Yue Yue; Shengkai Lin; Hanshitong Gu; Ziyi Han; Qingxia Li; Tao Tian; Xu Wei; Zhongxin Wu (Oceans, 2025)
The construction of artificial reefs is the primary ecological project of marine ranching and one of the most important methods of creating habitats for marine organisms. To date, studies on artificial reefs have taken a macroscopic perspective, with few studies having investigated the fungal communities in artificial reefs in the North Yellow Sea. Therefore, the aim of this study was to determine the distribution patterns of seawater quality, sediment properties, and fungal communities following the placement of artificial reefs of different materials in the North Yellow Sea. A sampling survey of marine ranching in the northern Yellow Sea was conducted in August 2023. Sediment and seawater samples were collected from the stone and concrete artificial reef areas as well as from the areas without constructed reefs as a control. Research shows that the total phosphorus (TP), total nitrogen (TN), and total organic carbon (TOC) concentrations were higher in the concrete reef than that in the other two regions. We obtained 735 fungal operational taxonomic units (OTUs) which were assigned to 11 phyla and 374 genera. Significant differences in the beta-diversity of the fungal communities were found among the three sampling regions, and the dominant species varied in seawater and sediment samples from different reef areas. Ascomycota was the most abundant phylum in the seawater and sediment samples, followed by Basidiomycota. pH and dissolved oxygen (DO) emerged as the most important factors affecting fungal communities in the seawater samples, whereas mean grain size, TN, and TOC had a significant effect on the communities in the sediments, with TP and TOC playing the most critical roles. Our study compared the characteristics of fungal communities in seawater and sediments in distinct types of artificial reefs and control areas, revealing the main environmental factors affecting fungal communities, which is of great significance for protecting biodiversity and evaluating the ecological effects of artificial reef placement.

Comparative analysis of indoor thermal environment characteristics and occupants’ adaptability: Insights from ASHRAE RP-884 and the Chinese thermal comfort database - Liu Yang; Feixiang Wang; Shengkai Zhao; Siru Gao; Haiyan Yan; Zhen Sun; Zhiwei Lian; Lin Duanmu; Yufeng Zhang; Xiang Zhou; Bin Cao; Zhaojun Wang; et al. (Energy and Buildings, 2024)

Regional ship collision risk prediction: An approach based on encoder-decoder LSTM neural network model - Chenyan Lin; Rong Zhen; Yanting Tong; Shenhua Yang; Shengkai Chen (Ocean Engineering, 2024)

Plant-mediated rhizospheric interactions in intraspecific intercropping alleviate the replanting disease of Radix pseudostellariae - Hongmiao Wu; Manhong Lin; Christopher Rensing; Xianjin Qin; Shengkai Zhang; Jun Chen; Linkun Wu; Yanlin Zhao; Sheng Lin; Wenxiong Lin (Plant and Soil, 2020)

Population transcriptomes reveal synergistic responses of DNA polymorphism and RNA expression to extreme environments on the Qinghai–Tibetan Plateau in a predatory bird - Shengkai Pan; Tongzuo Zhang; Zhengqin Rong; Li Hu; Zhongru Gu; Qi Wu; Shanshan Dong; Qiong Liu; Zhenzhen Lin; Lucia Deutschova; Xinhai Li; Andrew Dixon; et al. (Molecular Ecology, 2017)
Low oxygen and temperature pose key physiological challenges for endotherms living on the Qinghai–Tibetan Plateau ( QTP ). Molecular adaptations to high‐altitude living have been detected in the genomes of Tibetans, their domesticated animals and a few wild species, but the contribution of transcriptional variation to altitudinal adaptation remains to be determined. Here we studied a top QTP predator, the saker falcon, and analysed how the transcriptome has become modified to cope with the stresses of hypoxia and hypothermia. Using a hierarchical design to study saker populations inhabiting grassland, steppe/desert and highland across Eurasia, we found that the QTP population is already distinct despite having colonized the Plateau cDNA level, but of only seventeen genes identified, three function in hypoxia and four in immune response. Our results show a significant role for RNA transcription: 50% of upregulated transcription factors were related to hypoxia responses, differentiated modules were significantly enriched for oxygen transport, and importantly, divergent EPAS 1 functional variants with a refined co‐expression network were identified. Conservative gene expression and relaxed immune gene variation may further reflect adaptation to hypothermia. Our results exemplify synergistic responses between DNA polymorphism and RNA expression diversity in coping with common stresses, underpinning the successful rapid colonization of a top predator onto the QTP . Importantly, molecular mechanisms underpinning highland adaptation involve relatively few genes, but are nonetheless more complex than previously thought and involve fine‐tuned transcriptional responses and genomic adaptation.